2020
DOI: 10.18632/oncotarget.27609
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer effect of physical activity is mediated by modulation of extracellular microRNA in blood

Abstract: Epidemiological studies provide evidence that physical activity reduces the risk of cancer, particularly of breast cancer. However, little is known about the underlying molecular mechanisms as related to microRNAs. The goal of the herein presented study is to explore the involvement of miRNAs in beneficial effects exerted by physical activity in breast cancer prevention. Thirty subjects (mean age: 57.1 ± 14.7 years) underwent 45 minutes of treadmill walking under standardized conditions. The levels of extracel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Exercise was shown to modulate the expression of several miRNA species that in turn are protective against cancer ( Li et al, 2020 ; Pulliero et al, 2020 ). In our report we demonstrate this modulation observed after both short-term (0.5 year) and long-term (25 + years) regular exercise since our miR-23a, 451a, 223-3p, and miR-150-5p were all suppressed emphasizing the role of exercise in the prevention of several cancer entities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Exercise was shown to modulate the expression of several miRNA species that in turn are protective against cancer ( Li et al, 2020 ; Pulliero et al, 2020 ). In our report we demonstrate this modulation observed after both short-term (0.5 year) and long-term (25 + years) regular exercise since our miR-23a, 451a, 223-3p, and miR-150-5p were all suppressed emphasizing the role of exercise in the prevention of several cancer entities.…”
Section: Discussionmentioning
confidence: 99%
“…In our report we demonstrate this modulation observed after both short-term (0.5 year) and long-term (25 + years) regular exercise since our miR-23a, 451a, 223-3p, and miR-150-5p were all suppressed emphasizing the role of exercise in the prevention of several cancer entities. Nevertheless, data on exercise-derived exosomal miRNA species in modulating cancer prevention is still in its infancy ( Pulliero et al, 2020 ). Therefore, elaborate research effort is required to reveal the role of exosomal miRNA species in this particular field.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it has been suggested that this miRNA can translocate from skeletal muscle to circulation and to cancer cells, where it acts as an exercise-induced systemic factor downregulating tumor progression. Moreover, Pulliero, You ( Pulliero et al, 2020 ) showed that an exercise bout modulates the expression of 14 c-miRNAs involved in pathways relevant to the control of cancer development and progression (e.g., oncogene and metastasis suppression, cell proliferation, apoptosis, cancer invasion) in healthy postmenopausal women (54–78 years old). Specifically, c-miR-206 and c-miR-30c expression were upregulated and downregulated, respectively.…”
Section: Acute Vs Chronic Effect Of Exercise Training On C-mirna Expr...mentioning
confidence: 99%
“…Apart from proteins, other factors like miRNA or metabolites, incorporated in EVs, are likely to play a role. It has been reported that several circulating miRNAs may mediate the beneficial effects of physical activity [91][92][93][94]. Amongst them, miR-206 was found to reduce breast cancer cell growth by slowing G1/S transition and inducing apoptosis in vitro.…”
Section: Evs In Physical Exercise-tumor Cross-talkmentioning
confidence: 99%
“…Amongst them, miR-206 was found to reduce breast cancer cell growth by slowing G1/S transition and inducing apoptosis in vitro. Myoblasts that were stimulated by gravity to simulate physical activity were shown to release miRNA-microvesicles containing miR-206 [91]. Others have found miR-206 to be associated with the modulation of inflammation [95] and the promotion of antiangiogenic effects in exercising breast cancer patients [96].…”
Section: Evs In Physical Exercise-tumor Cross-talkmentioning
confidence: 99%